Implementation of Sanctions Against Perpetrators of Child Trafficking Crimes at the Argamakmur District Court - Rio Nugroho; Dwikari Nuristiningsih; Ependi, Ependi (Fox Justi : Jurnal Ilmu Hukum, 2025)
The problem of child trafficking has complex ethical, social and legal dimensions, making it one of the most serious human rights violations. Forced labor, sexual exploitation and other forms of exploitation that undermine children's futures are all too common, and children are the most vulnerable victims. The purpose of this study was to understand the application of criminal sanctions for perpetrators of child trafficking in the Argamakmur District Court and to identify obstacles faced in the process. The method used was the empirical law type (socio-legal) juridical-sociological approach. Data were obtained through direct interviews with judges, perpetrators, and victims, as well as studies of court decision documentation. This study resulted in the implementation of penalties for those who commit this crime based on the provisions of the law that have been enacted, especially Law Number 35 of 2014 concerning Child Protection. However, the sanctions imposed are still relatively light and do not fully reflect substantive justice, because they only use one article of the law, even though the perpetrators carry out economic and sexual exploitation. Obstacles in the application of sanctions include the lack of understanding of law enforcement officers regarding the relevant articles, limited evidence, minimal reporting, and social factors such as pressure on victims. This study recommends the need for special training for the part that enforces the rules and strengthens each agency in handling child trafficking cases.